Unidirectional synchronization of Jerk circuit and it’s uses in secure communication system - Fatma Susilawati, Mohamad; Mustafa, Mamat; Aceng, Sambas (Hikari Ltd., 2015)
Information is masked by chaotic signals at the transmitter, and then sent to the receiver by the public channel. Finally the encrypted signals are decrypted at the receiver. In this scheme, the key issue is that the two identical chaos generators in the transmitter end and the receiver end need to be synchronized. In this paper, in order to show some interesting phenomena of three dimensional autonomous ordinary differential equations, the chaotic behavior as a function of a variable control parameter, has been studied. The initial study in this paper is to analyze the phase portraits, the Lyapunov exponents, the Poincaré maps and the bifurcation diagrams. Moreover, some appropriate comparisons are made to contrast some of the existing results. Finally, the effectiveness of the unidirectional coupling scheme between two identical Jerk circuits in a secure communication system is presented in details. Finally, the simulation and the experimental results are shown to demonstrate that the proposed method is correct and feasible.